2007
DOI: 10.4049/jimmunol.179.7.4367
|View full text |Cite|
|
Sign up to set email alerts
|

Ambient Ozone Primes Pulmonary Innate Immunity in Mice

Abstract: Exposure to ozone in air pollution in urban environments is associated with increases in pulmonary-related hospitalizations and mortality. Because ozone also alters clearance of pulmonary bacterial pathogens, we hypothesized that inhalation of ozone modifies innate immunity in the lung. To address our hypothesis, we exposed C57BL/6J mice to either free air or ozone, and then subsequently challenged with an aerosol of Escherichia coli LPS. Pre-exposure to ozone resulted in enhanced airway hyperreactivity, highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 54 publications
10
48
1
Order By: Relevance
“…S1), representing 157-271% increased airway resistance over filtered air (FA) controls at baseline. This model has been used successfully in multiple laboratories (34,37,38). A recent report (39) showed the kinetics (6-48 h after exposure) of inflammation and robust AHR development to methacholine (MCh) 24 h after O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…S1), representing 157-271% increased airway resistance over filtered air (FA) controls at baseline. This model has been used successfully in multiple laboratories (34,37,38). A recent report (39) showed the kinetics (6-48 h after exposure) of inflammation and robust AHR development to methacholine (MCh) 24 h after O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many epidemiological and experimental studies have shown that individuals with pre-existing inflammatory conditions are more prone to the adverse effects of environmental injury. [15][16][17] Indeed, aggravation of pre-existing inflammation has been documented after exposure to particulate air pollution and various types of nanoparticles. [18][19][20][21] This study was designed to investigate the inflammationmodulating effects of CeO 2 nanoparticles in human peripheral blood monocytes at noncytotoxic exposure concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model, preexposure to nonlethal concentrations of ozone was shown to prime the innate immune system, resulting in an increased Toll-like receptor-4-mediated response to subsequent stimulation with inhaled endotoxin (10). Chronic environmental ozone exposure in humans may have a similar effect, enhancing Toll-like receptor-4-mediated inflammatory signaling in the lung.…”
Section: It's In the Air We Breathementioning
confidence: 86%